(untitled) (Asian Education Studies, 2022)
This paper studies types and characteristics of the teacher classroom feedback through the investigation of 22 classes of 22 senior high school English teachers. Non-participatory observation method was adopted to examine types and characteristics of teacher feedback based on the videos of the 11th National Senior High School English Teaching Demonstration. The purpose of this study is to find out existing problems of teacher feedback so as to improve senior high school English teachers’ teaching ability. According to classroom observation and data analysis, the types of the teacher feedback include positive feedback, negative feedback and multiple feedback. The characteristics of the teacher feedback are as follows: among 3 feedback types, positive feedback is the most frequently used one and negative feedback is often used with positive feedback. The existing problems in teachers’ feedback are: general feedback including matter-of-fact praise and general praise is often given by teachers; students are often interrupted by teacher feedback; the teacher feedback focuses more on form of student language than on meanings of interaction between teachers and students. In terms of the types, characteristics and problems of teacher feedback, this study gives some suggestions for English teachers in senior high schools to develop their teaching ability of giving feedback.